The syncline and anticline nature of poverty among farmers: Case of cashew farmers in the Jaman South District of Ghana. Issue 4 (4th July 2018) - Peprah, Prince; Amoako, Jones; Adjei, Prince Osei-Wusu; Abalo, Emmanuel Mawuli
ABSTRACT: This article sought to empirically find out factors behind the rising and falling nature of poverty among rural cashew farmers in the Jaman south district of the Brong Ahafo Region. A sample size of 160 cashew farmers were selected for the study. It was established that nine (9) major factors contribute to the rising level of poverty among the respondents at some point in the year. It is recommended that cashew farmers should be encouraged by the district assembly and other stakeholders to save during the harvesting season as well as borrow from the banks if the need be.